Cashing in for Growth : Corporate Cash Holdings as an Opportunity for Investment in Japan - Sher, Galen (IMF Working Papers; Working Paper, 2014)
Over the last two decades, cash holdings in nonfinancial firms around the world have increased. This phenomenon is particularly concerning in Japan, where the success of Abenomics depends on a transition from stimulus-driven to self-sustaining growth based on private consumption and investment. This paper finds that Japanese nonfinancial firms have accumulated cash at the expense of investment and dividends, hampering this transition. The evidence suggests that cash accumulation is due to financial imperfections combined with rising corporate profitability and uncertainty, while corporate governance plays only a limited role. These firms have cash holdings available for investment of about 5 percent of GDP. Policy options for encouraging the use of these cash holdings include improving firms' access to market-based financing and discouraging CEO duality.